(3cJGH HjdjfGS aj JBKjQ GdQhMGfjGJ hGdeQcHGJ hCYeGd GdUhQ hOaY GdCeQGV hMdhdgGs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s; (3HdjfGS GdMcjes
(3ChdgG (B:s
(3Ef GdadGSaI bO hVYhG ChVGYkG ai Yde GdchGcH hCHGfhYf SYhOgG hcdh Ydi fMhjJgG s
(3BNQgG (B:s
(3hgheJeRL HjfgG , jchf eY GdfMS GdCcHQ fMSkG, heY GdSYO GdCcHQ SYOkG s
(3GdeNWhW GdCUdi JQLeI HdjfGS GdMcjes
(3JHUQI GdYfhGf (B:s
(3JQLeI(B/(3fbds
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B157 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMQha h GdChaGbs